Making love : sentiment and sexuality in eighteenth-century British literature - Kelleher, Paul (Transits (Bucknell University), 2015)
Examines how writers of 18th century English sentimental literature came to consider love between a husband and wife to be A (or possibly THE) source for sympathy and benevolence, removing those experiencing it from the self-centeredness of current philosophical and economic theory. Homosexual desire, therefore for these writers came to be considered as a barrier to attaining sympathy, sentiment, and benevolence.